Pengaruh Keterlibatan Pendampingan Orang Tua dan Motivasi dalam Belajar Terhadap Prestasi Belajar Siswa Kelas IV SD Negeri Se-Kecamatan Bayan Tahun Ajaran 2021/2022 - Kholifah Nurul Hidayah; Kartika Chrysti Suryandari; Wahyudi Wahyudi (Universitas Sebelas Maret, 2022)
This study aims to determine the positive influence of: (1) the involvement of parental assistance on learning achievement; (2) learning motivation on learning achievement; and (3) the involvement of parental mentoring and motivation on learning on the learning achievement of fourth grade elementary school students in Bayan District for the 2021/2022 academic year. This research is quantitative research with correlation using multiple linear regression analysis. The sampling was carried out using a cluster random sampling technique, with a sample of 288 students from a population of 642 fourth grade students at State Elementary Schools in Bayan District for the 2021/2022 academic year. The results of this study indicate that there is a positive influence between: (1) the involvement of parental assistance in learning on learning achievement (tcount = 4,588 > ttable = 1,968) with a contribution of 10.18%; (2) learning motivation on learning achievement (tcount = 2,998 > ttable = 1,968) with a contribution of 5.80%; and (3) parental assistance and motivation in learning on learning achievement (Fcount = 28.238 > Ftable = 3.027) with a contribution of 15.98%. Based on the results of the study, it can be concluded that the involvement of parental assistance and motivation in learning has a positive effect on the learning achievement of fourth grade students of State Elementary Schools in Bayan District in the 2021/2022 academic year.Keywords: Parental Assistance, Motivation, Learning Achievement Penelitian ini bertujuan untuk mengetahui adanya pengaruh positif dari: (1) keterlibatan pendampingan orang tua dalam belajar terhadap prestasi belajar; (2) motivasi belajar terhadap prestasi belajar; serta (3) keterlibatan pendampingan orang tua dan motivasi dalam belajar terhadap prestasi belajar siswa kelas IV SDN se-Kecamatan Bayan tahun ajaran 2021/2022. Penelitian ini merupakan penelitian kuantitatif dengan korelasi menggunakan analisis regresi linier berganda. Pengambilan sampel dilakukan dengan teknik cluster random sampling yaitu dengan sampel 288 siswa dari populasi 642 siswa kelas IV SDN se-Kecamatan Bayan tahun ajaran 2021/2022. Hasil penelitian ini menunjukkan bahwa terdapat pengaruh positif antara: (1) keterlibatan pendampingan orang tua dalam belajar terhadap prestasi belajar (thitung= 4,588 > ttabel = 1,968) dengan sumbangan 10,18%; (2) motivasi belajar terhadap prestasi belajar (thitung= 2,998 > ttabel = 1,968) dengan sumbangan sebesar 5,80%; serta (3) pendampingan orang tua dan motivasi dalam belajar terhadap prestasi belajar (Fhitung= 28,238 > Ftabel = 3,027) dengan sumbangan sebesar 15,98%. Berdasarkan hasil penelitian tersebut, dapat disimpulkan bahwa keterlibatan pendampingan orang tua dan motivasi dalam belajar berpengaruh positif terhadap prestasi belajar siswa kelas IV SDN se-Kecamatan Bayan tahun ajaran 2021/2022.Kata kunci: Pendampingan Orang Tua, Motivasi, Prestasi Belajar